Chapter Il ruolo dell'utopia, del mito e dell'immaginario nella concezione della geografia di Massimo Quaini - Surdich, Francesco (Territori, 2021)
Myth, utopia and the imaginary have represented fundamental categories of geographical thought, as Massimo Quaini highlighted in several of his contributions, which underlined their influence and importance for the history of geography in the construction and development of geographical concepts. The weight and role of these categories of interpretation of geographical reality were particularly important at the time of the great geographical discoveries in the process of opening the European horizon to new worlds, a complex process in which the geographical imaginary represented a stimulus and a push, as it happened for the genesis and development of the Colombian conceptual universe.